The nursing process: a time to remember its purpose - T. Heather Herdman (Universidade Federal do Ceará, 2013)
We have a problem. Somehow, along the way, we lost track of what the nursing process is supposed to represent. Organizations produce documentation (often lots of paper or many computer screens of data) incorporating nursing assessment, diagnoses/patient problems, interventions and outcomes which meet the requirements of accrediting organizations and regulatory bodies. However, ask the nurses what they think about the nursing process and you will often see eyes rolling, and hear complaints about the amount of time it takes "to do" the nursing process. It is a requirement that seems to be without benefit or purpose to many in practice.